Gambaran Kadar Hemoglobin Pada Penderita Tuberkulosis Paru Di Uptd Rumah Sakit Khusus Paru Provinsi Sumatera Utara - Sembiring, Terang U; Erlan Aritonang; Denrison Purba; Malemta Tarigan; Agnes Sawinda; Winda Irawati Zebua (Universitas Sari Mutiara Indonesia, 2024)
Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis. Tuberculosis is an infectious disease that can cause various complications, one of which is anemia. Anemia is charaterized by a decrease in hemoglobin levels, a protein in red blood cells thet gives blood its red color. This decrease in hemoglobin levels in tuberculosis patients can be caused by poor nutrional status. The aim of this study was to determine the hemoglobin levels in pulmonary tuberculosis patients at the UPTD Special Paru Hospital of North Sumatera Province. This descriptive study aimed to describe the hemoglobin levels in pulmonary tuberculosis patients who met the petermined sample criteria. A total of 20 pulmonary tuberculosis patients who underwent hemoglobin examination were random selected. Hemoglobin examination was performed using a hematology analyzer. The result showed that 9 patients (45%) had hemoglobin levels below normal values, while 11 patiens (55%) had normal hemoglobin levels. As for the conclusion of this study,most new TB sufferers are found with normal HB levels. The advice is that all those with lung Tuberculosis should do a complete examination so that the sufferer can know his body health and maintain a healthy pattern of life.